The Relationship between Artificial Intelligence (AI) Quality, Customer Preference, Satisfaction and Continuous Usage Intention of e-Banking Services - Mohammed Aliyu Dantsoho; Kabiru Jinjiri Ringim; Kabiru Maitama Kura (Indonesian Business Review, 2021)
This study was set to examine the relationship between artificial intelligence (AI) quality, customer preference, satisfaction and continuous usage intention of e-banking services powered by AI solution. To achieve this, a cross-sectional research design was employed to collect data from the bank customers using purposive snowball sampling. In total 274 responses were retrieved from the bank customers that agreed to participate in the study and 246 were useful for the final data analysis. Analysis was done using partial least square structural equation modeling (PLS-SEM) approach with aid of SmartPLS 3.2.8. A snowball non-probability sampling procedure was used for the data collection. The findings indicate that the AI quality have a positive effect on satisfaction and satisfaction has significant positive effect on the intention of continuing use of e-banking services. However, consumer preference was not significantly related to continuous usage intention of e-banking services. This is practically possible in Nigerian context. Because we observe that majority of the respondents does not have specific preference of using or interacting with e-banking services powered by AI as against those control by human interactions. The implication of this findings is that is the used of AI based services in the Nigerian context is still at it infancy level. Therefore, there is still much to learn from the experience of both planners, implementers and beneficiaries. This study is perhaps, the first of its kind to examine the relationships of AI chatbot quality on customer satisfaction and continuous usage intention of e-banking services. It is therefore, contributes to the development of literature in this direction.